Overproduction of SecA Suppresses the Export Defect Caused by a Mutation in the Gene Encoding the Escherichia coli Export Chaperone SecB - Cook, Heather A. (American Society for Microbiology, 1999)
SecB is a cytosolic protein required for rapid and efficient export of particular periplasmic and outer membrane proteins in Escherichia coli. SecB promotes export by stabilizing newly synthesized precursor proteins in a nonnative conformation and by targeting the precursors to the inner membrane. Biochemical studies suggest that SecB facilitates precursor targeting by binding to the SecA protein, a component of the membrane-embedded translocation apparatus. To gain more insight into the functional interaction of SecB and SecA, in vivo, mutations in the secA locus that compensate for the export defect caused by the secB missense mutation secBL75Q were isolated. Two suppressors were isolated, both of which led to the overproduction of wild-type SecA protein. In vivo studies demonstrated that the SecBL75Q mutant protein releases precursor proteins at a lower rate than does wild-type SecB. Increasing the level of SecA protein in the cell was found to reverse this slow-release defect, indicating that overproduction of SecA stimulates the turnover of SecBL75Q-precursor complexes. These findings lend additional support to the proposed pathway for precursor targeting in which SecB promotes targeting to the translocation apparatus by binding to the SecA protein.